ANALYSIS OF QUALITY RISK MANAGEMENT ON INBOUND TO OUTBOUND LOGISTICS ACTIVITIES WITH FMEA METHOD - Topaga, Petrus
Pharmaceutical logistics has experienced significant growth making it a priority industry being developed. However, there are still many issues related to unqualified drugs. This can happen because of a process failure in the business process. Risk management with FMEA as a basic step to help manufacture quality products. The risk management process at the author's work is still not done thoroughly so that the process that appears before making preparations. This condition is due to the absence of a risk management design and measurement tools to assess the current condition of a risk in pharmaceutical logistics comprehensively. In this research with a risk assessment, it is expected to provide an overview of inbound risk management to outbound logistics as a whole to planned contingencies so that a more robust process is produced. In addition, there is the development of a Risk Management Index (RMI) to provide parameters that underlie management's assessment in a comprehensive and open manner to identify strategic risks that have a major impact on the interests of consumers and the company's business. The research begins by making BPM at the next stage, which is followed by making Quality Risk Management (QRM) along with contingency plans, selecting strategic risks that are in line with Management and calculating RMI. The results of the BPM research at each stage and obtained a measuring instrument that is the RMI of the QRM design by 92%. From the QRM design, there are 12 Strategic Risk documents in 7 categories, namely acceptance accuracy, compliance, availability, On Time Fullfilment (OTIF), delivery conditions, conformity with goods, and product quality with 120 risks out of a total of 262 risks.